The effect of carrying a child in a baby sling on the movement system - Dąbrowska, Maria; Lisiecki, Jakub; Ulenberg, Agata; Ulenberg, Grzegorz (Journal of Education, Health and Sport, 2017)
More and more people use baby slings and wraps instead of wheelchairs. The child is in front of the person who wears them. The baby weight is distributed evenly and symmetrically. Carrying a baby in a sling is safe, doesn’t damage a locomotor system if the binding in a sling is good. Carrying a baby in a sling helps in treatment hip dysplasia and has a good outflow on the hip joints in infants.